Turkmen exodus to the Anatolia and establishing their pricipalities: "First half of the 11th century-beginning of the 12th century" - Hussein, Hazhar; Omar, Othman (Humanities Journal of University of Zakho, 2023)
The Turkmen exodus to the Anatolia is considered one of the important historical periods in the history of the Turks. After the tenth century, a number of the Turkish tribes had converted to Islam in the central Asia. Gradually they headed toward western of the central Asia, they migrated from Iran to Anatolia especially after the foundation of the Sajuq`s state in (1037). Afterwards, under the authority of the Saljuqs, the Turkmen started to migrate to Anatolia. At the same time, the Byzantine dynasty had internal conflicts that paved the way for the Seljuqs to take action and to head toward Anatolia. the first half of the 11th century, the Turkmen tribes attempted to settle down in Anatolia, but their attempts failed. While, in the second half of the 11th century, and after they defeated the Byzantins in the battle of Malazgirt, they could eventually make Anatolia their own home in (1071). Their victory in the battle led to the foundation the state of the Saljuq`s Rum in Anatolia. Consequently, some leader emerged from among the Turkmen tribes could build some emirates such as; Danishmandi, Saltuk, Mankochk, and Zackac.